Effect of surface treatments on damping behaviour of carbon fibre reinforced brake friction material. (5th September 2019) - Konada, Naresh Kumar; Sai, Suman Koka Naga
The damping behaviour of carbon fibre (CF) reinforced brake friction material depends mainly on the interfacial adhesion between fibre and matrix and ingredients selected for the friction material. The surface of CF is chemically inert in nature. Therefore, in this work CF surface is modified by different surface treatments to increase hydroxyl or carboxyl groups on its surface. An attempt is made to improve the bonding strength between CF and matrix by three treatment methods. CF surface is modified by surface oxidation, HNO3 and grafting multi walled carbon nano tubes functionalised (MWCNT-F) on CF surface. CF content after surface modification by three different treatments is varied in wt% (2%, 3%, 4% and 5%) and mixed with remaining ingredients. Friction composite sheets are fabricated by using hand layup method and characterised by SEM, TGA and FTIR analysis. MWCNTs-F on CF surface is observed. Sample specimens are cut from the friction composite sheets and damping behaviour of the specimens is evaluated by using Fast Fourier Transform analyser. The best combination of ingredients and surface treatment method is selected for the fabrication of friction material to reduce the squeal generation at the interface between brake disc and pad.